Implementation of 2-Inch Grading Technique for Making Blouse Pattern in Modest Business - Lubis, H (KnE Social Sciences, 2019)
This study aims to create a model to make patterns for modest customers in a faster way. The problem of this study is derived from the obstacles that are often experienced by modest entrepreneurs in making patterns for customers. The result of the study of implementing an individual pattern using grading system shows that there are several points that still need attention for further research. The instruments used are sheets of observation, with scales 3–1. These points are the position of the neck, waist, and shoulder lines. Meanwhile, the front length, appearance of the bust, hip, and dart side are already good. The output of this research is a model to make patterns for modest business, by applying pattern grading technique principles, for women’s blouses. The weakness of this study is that the pattern master is not built by standardized size because until now there has been no standard clothing size for Indonesian women. Keywords: 2-inch grading technique, master pattern, grading technique adjustment result blouse, modest